Towards a strategy for malaria in pregnancy in Afghanistan: analysis of clinical realities and women's perceptions of malaria and anaemia. (December 2015) - Howard, Natasha; Enayatullah, Sayed; Mohammad, Nader; Mayan, Ismail; Shamszai, Zohra; Rowland, Mark; Leslie, Toby
Abstract Background Afghanistan has some of the worst maternal and infant mortality indicators in the world and malaria is a significant public health concern. Study objectives were to assess prevalence of malaria and anaemia, related knowledge and practices, and malaria prevention barriers among pregnant women in eastern Afghanistan. Methods Three studies were conducted: (1) a clinical survey of maternal malaria, maternal anaemia, and neonatal birthweight in a rural district hospital delivery-ward; (2) a case–control study of malaria risk among reproductive-age women attending primary-level clinics; and (3) community surveys of malaria and anaemia prevalence, socioeconomic status, malaria knowledge and reported behaviour among pregnant women. Results Among 517 delivery-ward participants (1), one malaria case (prevalence 1.9/1000), 179 anaemia cases (prevalence 346/1000), and 59 low-birthweight deliveries (prevalence 107/1000) were detected. Anaemia was not associated with age, gravidity, intestinal parasite prevalence, or low-birthweight at delivery. Among 141 malaria cases and 1010 controls (2), no association was found between malaria infection and pregnancy (AOR 0.89; 95 % CI 0.57–1.39), parity (AOR 0.95; 95 % CI 0.85–1.05), age (AOR 1.02; 95 % CI 1.00–1.04), or anaemia (AOR 1.00; 95 % CI 0.65–1.54). Those reporting insecticide-treated net usage had 40 % reduced odds of malaria infection (AOR 0.60; 95 % CI 0.40–0.91). Among 530 community survey participants (3), malaria and anaemia prevalence were 3.9/1000 and 277/1000 respectively, with 34/1000 experiencing severe anaemia. Despite most women having no formal education, malaria knowledge was high. Most expressed reluctance to take malaria preventive medication during pregnancy, deeming it potentially unsafe. Conclusions Given the low malaria risk and reported avoidance of medication during pregnancy, intermittent preventive treatment is hard to justify or implement. Preventive strategy should instead focus on long-lasting insecticidal nets for all pregnant women.